Visions of a greener future for the Seil of Amman. Augmented Reality as an urban design tool - Janset Shawash; Narmeen Marji (Agathón)
In a context characterized by flooding and environmental degradation of the Seil of Amman (natural heritage of the capital of Jordan), caused by climate change, rapid urbanization and unsustainable stormwater management, the paper explores the potential of new Mobile Augmented Reality (MAR) technologies as a tool of public engagement with new ecologically sustainable urban regeneration projects. Therefore, two possible scenarios for a green/blue intervention in the Ras al-Ein area on the path of the Seil are presented, elaborated through a specially developed immersive mobile augmented reality software, describing both the application development process and the users’ response.